PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA DI KELAS VI SDN PARANG TAMBUNG 1 KOTA MAKASSAR - Yogi Cahyadi; Andi Adam; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine by analyzing the impact of the implementation of the teaching at the right level model problem based learning approach in improving student learning outcomes in mathematics. This research method uses the Classroom Action Research (CAR) method, this provides an opportunity to understand and analyze the planning, implementation and evaluation process and identify challenges and obstacles in improving student learning outcomes in mathematics in Class VI SDN Parang Tambung 1 Makassar City.This study went through several cycles, each cycle including planning, implementation, observation and reflection. The implementation of learning using the teaching at the right level model problem based learning approach adapts to each different student's abilities. This data was obtained through observation results and assessment of learning outcomes, this shows positive changes in student involvement in understanding the material. In addition, these initial results provide information faced by teachers in implementing learning from traditional teaching to the implementation of the teaching at the right level model problem based learning approach. The results of this study indicate an increase in student learning outcomes from cycle 1 of 0.25 with a low category and cycle 2 of 0.58 with a medium category. This shows that the application of teaching at the right level problem based learning model is able to improve student learning outcomes.